Pengaruh Penggunaan Modul Pembelajaran Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi di Kelas XI SMA Negeri I Suwawa Kabupaten Bone Bolango - Rustam Mooduto; Rosman Ilato; Fitri Hadi Yulia Akib (universitas negeri gorontalo, 2019)
This research aims at investigating in what extent the influenceof module learning utilization to word students learningachievement in economics subject at grade XI in SMANegeri 1 Suwawa, District of Bone Bolongo. Data have beencollected by distributing questionnaire to students of SMANegeri 1 Suwawa,District of Bone Bolongo therefore the dataare categorized as primary data.. Technique of data analysisis simple linear regression.Finding reveals that there is significant influence of learningmodule utilization toword students learning achievementin SMA Negeri 1 Sumawa, District of Bone Bolango. It canbe seen by determination coefficient is 0,211, the value indicatesthat for 21,1% of students learning achievement inSMA Negeri 1 Sumawa,District of Bone Bolango can be explainedby learning Module utilization while the rest 78,9%can be explained by other variables that are not observed inthis research.